Cerebrospinal fluid procalcitonin: a promising diagnostic tool in differentiating bacterial from aseptic meningitis - Ahmad, Mudasir; Ali, Syed Wajid; Iqbal, Javeed; Wani, Feroz Ahmad; Ahmad, Javeed (International Journal of Contemporary Pediatrics, 2019)
Background: Procalcitonin in cerebrospinal fluid has been evaluated with regard to its usefulness in distinguishing between the possible causative organisms for infections. CSF PCT as a diagnostic marker has also been evaluated for differentiating bacterial from viral meningitis with conflicting results obtained so far. The current study was designed to see the role of procalcitonin as diagnostic marker and in differentiating bacterial from aseptic meningitis in pediatric age group. Methods: Children from 5 months to 15 years of age who were suspected cases of meningitis and were admitted to Pediatric Department in SKIMS Srinagar, Jammu and Kashmir were included in this case control prospective study conducted from 2014 to 2016. The total number of 200 children participated in the study among which 100 were cases and 100 controls. Serum and CSF PCT was measured by a fluorescence immunoassay using QDX Instacheck with a detection limit of 0.25-100 ng/ml. Data was analyzed by using standard statistical tests using SPSS 20. Results: The mean CSF PCT in ng/ml in our study for viral meningitis was 0.59±0.43 (range=0.00-1.90), for bacterial meningitis 4.92±1.50 (range=2.89-10.82) and for controls 0.22±0.11 (range=0.00-0.32), respectively. CSF PCT was significantly higher in viral and bacterial meningitis as compared to controls (p<0.01) and significantly higher in bacterial meningitis as compared to viral meningitis (p<0.01). An AUC of 1.000 was established using serum and CSF PCT for bacterial meningitis. The diagnostic accuracy of serum and CSF PCT was almost 100% at cut-off of 2.2 ng/ml and 2.89 ng/ml, respectively. Conclusions: Author have concluded that CSF PCT can be used as a diagnostic marker with better results in differentiation of bacterial from aseptic meningitis.